Superficial heat administration and foam rolling increase hamstring flexibility acutely; with amplifying effects - Oranchuk, Dustin J.; Flattery, Matthew R.; Robinson, Tracey L. (Physical therapy in sport, 2019)
To compare the objective and subjective efficacy of three treatments on acute hip-flexion range of motion (ROM). Assessor-blind, randomized within-subject cross-over. University athletic training clinic. Twenty-two female collegiate lacrosse and soccer athletes. The passive straight-leg-raise (PSLR) was used to measure acute hip-flexion ROM pre- and post foam rolling (FR), superficial heating (SH), combination (SH + FR) and control treatments. A seven-point Likert scale statement measured the perceived effectiveness of each treatment. Superficial heat (+10.4%, ES = 0.78), FR (+7.26%, ES = 0.52), and SH + FR treatment (+12.9%, ES = 1.26) improved hip ROM when compared to the control (+2.4%, ES = 0.24) (all p < 0.001). The SH + FR treatment resulted in a greater improvement in hip ROM compared to FR (p = 0.001, ES = 0.95), whereas no significant difference was observed between the SH and FR (p = 0.083, ES = 0.68) or SH and SH + FR treatment (p = 0.270, ES = 0.43). SH + FR was perceived as more effective than FR (p = 0.033, ES = 1.21), but not SH (p = 0.193, ES = 0.63). However, only a moderately positive correlation (r = 0.508) between objective and subjective measures of hamstring flexibility was found. All treatments significantly improve hamstring flexibility with SH + FR being the most effective. Rehabilitation professionals should practice caution when relying on athlete perception and should prescribe treatments on an individual basis. •Range of motion and perceived efficacy were assessed following four conditions.•Superficial heat, foam rolling, and heat + rolling improvements were superior to the control.•The heat + rolling had the largest effect and was perceived to be most effective.•Moderate correlations between actual and perceived effectiveness were found.•Treatments should be prescribed on an individual basis where possible.